2023
DOI: 10.1002/advs.202202519
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Reprogramming of NK Cells by Black Phosphorus Quantum Dots Potentiates Cancer Immunotherapy

Abstract: Low persistence, metabolic dysfunction in microenvironment, and tumor-derived immunosuppression of Natural killer (NK) cells in patients are greatly limited the successful clinical application of NK cell-based cancer immunotherapy. Interestingly, herein that human serum albumin-encapsulated black phosphorus quantum dots (BPQDs@HSA) can effectively augment antitumor efficacy of clinical patients-derived NK cell immunotherapy is found. As the donor of phosphate group, BPQDs@HSA binds with the protein of phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…108,109 To enhance the NK cell-mediated innate antitumor immunity by reprogramming its cellular metabolism, a immunosensitizer (BPQDs@HSA) was constructed by encapsulating black phosphorus (BP) quantum dots (QDs) in human serum albumin (HSA) (Figure 5A, Table 2). 110 In this study, the author found that the BPQDs@HSA treatment enhanced the expression of TLR-5, TLR-9, and NF-ĪŗB in NK cells (Figure 5B). Notably, activation of NF-ĪŗB signaling was found to upregulate the secretion of cytokines (e.g., IFN-Ī³) by NK cells while decreasing the secretion of immune suppressive factors, such as IL-10 and TGF-Ī² (Figure 5C).…”
Section: Rewriting Glycolysis In Tumor Cellsmentioning
confidence: 60%
See 1 more Smart Citation
“…108,109 To enhance the NK cell-mediated innate antitumor immunity by reprogramming its cellular metabolism, a immunosensitizer (BPQDs@HSA) was constructed by encapsulating black phosphorus (BP) quantum dots (QDs) in human serum albumin (HSA) (Figure 5A, Table 2). 110 In this study, the author found that the BPQDs@HSA treatment enhanced the expression of TLR-5, TLR-9, and NF-ĪŗB in NK cells (Figure 5B). Notably, activation of NF-ĪŗB signaling was found to upregulate the secretion of cytokines (e.g., IFN-Ī³) by NK cells while decreasing the secretion of immune suppressive factors, such as IL-10 and TGF-Ī² (Figure 5C).…”
Section: Rewriting Glycolysis In Tumor Cellsmentioning
confidence: 60%
“…Data were expressed as mean Ā± SD (* p < 0.05, ** p < 0.01). Reproduced with permission from ref . Copyright 2023 Wiley-VCH.…”
Section: Nanomedicines For Glucose Metabolism Interventionmentioning
confidence: 99%
“…7(g)). 114 BPQDs@HSA binds to PIP5K1A proteins, activating downstream PI3K-Akt and mTOR signaling pathways, reprogramming cellular glycolytic metabolism, and further promoting oxidative phosphorylation, thereby maintaining cell viability and immunity to NK cells. Multi-omics analysis showed that proteins associated with NK cell immune function were significantly upregulated by BPQDs@HSA (Fig.…”
Section: Photonic Nanoplatform For Cutting-edge Precision Treatmentmentioning
confidence: 99%
“…Subsequently, the downstream NF-ĪŗB signaling pathway was activated, which could regulate the cytokine release and finally enhance the antitumor immune response. 72 3.4. Disturbance and Recovery of Kidney Function.…”
Section: Immunological Effectsmentioning
confidence: 99%
“…Similarly, BPDs were encapsulated into human serum albumin (HSA) by Chen et al, which could initiate the immune activation of natural killer (NK) cells by interacting with a Toll-like receptor (TLR) and upregulating the expression of mTOR. Subsequently, the downstream NF-ĪŗB signaling pathway was activated, which could regulate the cytokine release and finally enhance the antitumor immune response …”
Section: Cytotoxicity and Biological Responses Induced By Nano-bpsmentioning
confidence: 99%